Censorship and student communication in online and offline settings - Oluwole, Joseph; Green, Preston C., III (Preston Cary); IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book is a comprehensive reference source that addresses the issues surrounding student's right to free speech in on and off-campus settings and featuring relevant coverage on the implications of digital media as well as constitutional and legal considerations"--Provided by publisher.
Background -- True threat -- Fighting words -- Defamatory speech -- Obscene speech -- Child pornography -- Material and substantial disruption/infringement of rights -- Lewd, vulgar, plainly-offensive, and obscene speech -- School-sponsored speech -- Advocacy of illegal drug use -- Their stories: offline off-campus speech -- Their stories: online off-campus speech -- Assessing the current jurisprudence -- Acceptable use policies -- State anti-bullying statutes and student speech -- Forging the path forward from censorship.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 10/03/2015).
Keywords: Freedom of speech -- United States; Students -- Legal status, laws, etc. -- United States; Censorship -- United States; Internet -- Censorship -- United States; Intellectual freedom -- United States; Acceptable use policies; Anti-bullying concerns; Child pornography speech; Defamatory speech; Fighting words jurisprudence; Illegal drug use; Infringement of rights; Material and substantial disruption; Obscene speech; School-sponsored speech; Electronic books